Carbon Footprint of Conventional and Online Alternatives of National Scientific Student Conference in Hungary - Andras Polgar; Veronika Elekné Fodor (Chemical Engineering Transactions, 2023)
The carbon footprint shows the total - direct and indirect - greenhouse gas emissions of a person, organization, event or product in terms of CO2 equivalent. The carbon footprint of the alternatives of the Economics Section of the 35th National Scientific Student Conference in Hungary was examined. Environmental inventory data was collected in two event formats – conventional and online – via the activity and process approach. The main processes were mobility, accommodation, catering, energy, materials used, transport, and waste. The carbon footprint of the conference alternatives was calculated to compare the versions and to study and interpret CO2 savings. The methodology of the “MyClimate Foundation - The Climate Protection Partnership” was employed for the calculation. It can be concluded that the implementation of the online conference resulted in a saving of 90.57 % in terms of CO2 equivalent. The analysis indicates the critical points for the main processes. The transport of the participants (68 %) was the most significant contribution to the carbon footprint in the conventional conference, while in the case of an online conference, it was the self-catering (97 %). If catering is excluded, which was considered to be the same for both online and offline, the energy needs for the operation of electronic devices form the most significant part of the carbon footprint (98 %).